TECHNOLOGY DESCENT IN ONE STEP INTERMEDIATE COLUMN, WEIGHT OF WHICH EXCEEDS LOAD CAPACITY OF DRILLING RIGS (Academic journal Industrial Machine Building Civil Engineering, 2017)
Decrease quantity of sections of the casing saves time and money in the process offastening of the well. The need to use the sectional descent columns caused by a not sufficientcapacity drilling rigs, mainly. In addition, casings domestic and imported can not withstand theloads created by the weight of its own huge casing. In general, to address the issue ofdevelopment reduce the quantity of sections descent columns are developing in two directions:increasing the carrying capacity of drilling rigs, the creation of special jacks for runningcasing; increasing buoyancy force acting on the column in the wash liquid. The first wayallows for the descent into the well casing heavy and has only one limitation on unscrews loadsin threaded connections. In applying of welded columns is limiting the tensile stresses alongthe pipe. The second way is more technically difficult and needs of additional equipment casingand introduces additional limitations. The first method shutter casing at one time is limited andthe real unscrew load. In the second method sectional casing shutter is reduced by 30 – 60%.Keywords: drilling column, borehole, drilling fluid, centralizer.